2014
DOI: 10.1017/s0033291714002931
|View full text |Cite
|
Sign up to set email alerts
|

Minor physical anomalies and craniofacial measures in patients with treatment-resistant schizophrenia

Abstract: These findings suggest that certain MPAs and craniofacial features may serve as useful markers for identifying TRS at early stages of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…As a group, MPAs include subtle malformations in the craniofacial region and limbs, such as hypertelorism, low‐set ears, single palmar crease, curved fifth digit, and measurements of head circumference, maximum skull length, and skull base width that are outside of expected ranges. A recent study in patients with SCZ showed that treatment‐resistant patients could be characterized by a lower facial width and an increased lower facial height (Lin et al, ), indicating a potential clinical application of MPAs.…”
mentioning
confidence: 66%
“…As a group, MPAs include subtle malformations in the craniofacial region and limbs, such as hypertelorism, low‐set ears, single palmar crease, curved fifth digit, and measurements of head circumference, maximum skull length, and skull base width that are outside of expected ranges. A recent study in patients with SCZ showed that treatment‐resistant patients could be characterized by a lower facial width and an increased lower facial height (Lin et al, ), indicating a potential clinical application of MPAs.…”
mentioning
confidence: 66%
“…The neurodevelopmental theory of schizophrenia proposes that disrupted normal development, in utero or early infancy, leads to deficits in psychophysiological and neurological functioning in childhood or early adolescence, and eventually to prodromal or diagnostic symptoms of schizophrenia (Jablensky et al, 2017;Murray et al, 2017). Previous research has linked characteristics of abnormal development with TRS; higher rates of minor physical anomalies (Lin et al, 2015), more neurological soft signs (de Bartolomeis et al, 2018), poor verbal intelligence and fluency (Kravariti et al, 2018), and poor verbal memory (Joober et al, 2002;de Bartolomeis et al, 2013). None of the studies in this review included variables measuring physiology during development or cognition at the first episode.…”
Section: Discussionmentioning
confidence: 99%
“…[54] EOS also tends to be more treatment-resistant, [34] and may reflect a more severe form of the disorder associated with a greater genetic predisposition than AOS. [55] In the current study, all MPA-based models showed greater predictive validity for EOS than AOS, and familial aggregation was higher in first-degree relatives of EOS patients, supporting a neurodevelopmental model where childhood/adolescent-onset schizophrenia may represent a more malignant disorder caused by more severe in utero neurodevelopmental disruption (as reflected by MPAs) due to greater genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitatively measured MPAs and quantitatively measured craniofacial features compiled from the Waldrop scale and other previous scales were measured as described. [34] The scale for qualitative measurement of MPAs was based on that developed by Ismail et al and included 41 items. The morphological anomalies examined were located in 6 different body regions: head, eyes, ears, mouth, hand, and feet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation